El retrato colectivo de los Banu Birzal - De Felipe, Helena (Anaquel de Estudios Árabes, 2025)
The aim of this paper is to reconstruct the collective portrait of the Banū Birzāl, a Berber nukkārite group that was exiled from the Maghrib to al-Andalus during the caliphate of al-Ḥakam II. The objective of this reconstruction is to highlight the effects that the changes in geographical, socio-political and religious contexts provoked in their collective biographical portrait, which, in certain periods, is transferred from the collectivity to certain individualities. The collective displacement of Banū Birzāl and the details of their historical trajectory allow us to draw some conclusions about their textual representation as a group, changes in both their leadership and their beliefs and, finally, about their mobility in the Mediterranean area.
Keywords: Banu Birzal -- Histoire; Nukkarisme -- Andalousie

بنو برزال الأباضيون في الأندلس - بوخاري, عمر (مجلة الدراسات التاريخية والاجتماعية, 2020)
Keywords: Banu Birzal -- Histoire; Ibadisme -- Andalousie; Nukkarisme -- Andalousie

Bandits, apostates, or rebels? Ibadis in Abu l-Walid al-Baji's Kitab al-Muntaqà (al-Andalus, d. 474/1081) - Ruano, Delfina Serrano (11th Conference on Ibadi Studies "(Sacred) texts and (social) contexts" Text analysis and hermeneutics in Ibāḍī society and tradition, 2021)
Keywords: Nukkarisme -- Andalousie